Restructuring female identity through the Kristevan approach in Adrienne Rich’s selected poetry - Hassan, Mohamad Fleih (2017)
Adrienne Rich (1929-2012), a radical feminist poet in the United States, was credited with her power of using language as a medium to give voice to women who are marginalized by patriarchy. Thereby, female identity became a recurrent theme in her poetry. However, Rich’s discourse of female identity has been highly radicalized due to her extreme attitudes towards patriarchal thought. Hence, her poetry has been approached within the confines of the Queer theory. Thus, the first objective of this study is to explore the role played by the signifying system of the symbolic language in depriving women of their own female identities in the light of the patriarchal discourse of identity formation in Rich’s early poetry. The second objective is to examine the articulation of the semiotic elements in Rich’s poems and their role in disrupting the symbolic signifying system of language, which would lead to the circulation of new meanings that reflect women’s needs and desires and help in re-structuring female identity. The third objective is to explore Rich’s discourse of desire in selected poems in light of Kristeva’s concept of Abjection in order to resituate the female desire in relation to the dominant heterosexual thought as an active, and transgressive variable in the reconstruction of female identity. The study relies on Kristeva’s Revolution in Poetic Language (1984), utilizing the concepts of The Semiotic and The Symbolic to explore the power of the semiotic in troubling the symbolic system of signification. Kristeva thinks that the Semiotic and the Symbolic aspects of language are completing each other in the signifying process of the speaking subject. Moreover, the study relies again on Kristeva’s Powers of Horror: An Essay on Abjection (1982), to deal with the abject representation of female desire as a transgressive force for the heterosexual thought. Selections of Rich’s A Change of World (1951), A Snapshots of a Daughter-in-Law (1963), Necessities of Life (1966), Diving into the Wreck (1973), and The Dream of Common Language (1978) are chosen for the study to cover the different stages in Rich’s career. The study concludes that the articulation of the semiotic elements ‘maternal emotions and drives’ into the symbolic system of signification will generate new signifying system that helps in circulating a new discourse of female identity formation. Moreover, it concludes that Rich’s re-orientation of female desire was a technique to turn female desire into an active and transgressive variable in the reconstruction of female identity.